MSC-Derived Exosome Promotes M2 Polarization and Enhances Cutaneous Wound Healing - Xiaoning He; Zhiwei Dong; Yina Cao; Han Wang; Shiyu Liu; Li Liao; Yan Jin; Lin Yuan; Bei Li (Stem Cells International)
Mesenchymal stem cell transplantation (MSCT) promotes cutaneous wound healing. Numerous studies have shown that the therapeutic effects of MSCT appear to be mediated by paracrine signaling. However, the cell-cell interaction during MSCT between MSCs and macrophages in the region of cutaneous wound healing is still unknown. In this study, early depletion of macrophages delayed the wound repair with MSC injection, which suggested that MSC-mediated wound healing required macrophages. Moreover, we demonstrated that systemically infused bone marrow MSCs (BMMSCs) and jaw bone marrow MSCs (JMMSCs) could translocate to the wound site, promote macrophages toward M2 polarization, and enhance wound healing. In vitro coculture of MSCs with macrophages enhanced their M2 polarization. Mechanistically, we found that exosomes derived from MSCs induced macrophage polarization and depletion of exosomes of MSCs reduced the M2 phenotype of macrophages. Infusing MSCs without exosomes led to lower number of M2 macrophages at the wound site along with delayed wound repair. We further showed that the miR-223, derived from exosomes of MSCs, regulated macrophage polarization by targeting pknox1. These findings provided the evidence that MSCT elicits M2 polarization of macrophages and may accelerate wound healing by transferring exosome-derived microRNA.